Research handbook on civil-military relations - Croissant, Aurel; Kühn, David; Pion-Berlin, David (Elgar Handbooks in Political Science Series, 2024)
Bringing together leading scholars from across the world, this comprehensive Research Handbook analyses key problems, subjects, regions, and countries in civil-military relations. Showcasing cutting-edge research developments, it illustrates the deeply complex nature of the field and analyses important topics in need of renewed consideration.